The Effect of Learning in the New Normal Period of the Covid-19 Pandemic in Improving Early Childhood Discipline (Indonesian Journal of Early Childhood Education Studies, 2022)
The purpose of this study was to determine the effect of learning in the new normal period in the Covid-19 pandemic on the disciplinary character of early childhood. The methodology in this study uses descriptive quantitative data collection methods using observation sheets. The research sample amounted to 30 students in early childhood, data analysis using the product moment correlation formula. The results show that there is an effect of Learning in the New Normal Period of the Covid-19 Pandemic in improving early childhood discipline at SBB CERIA PAUD, as evidenced by the greater correlation calculation value, namely 0.333 > 0.312. Other findings, from several obstacles faced, namely: Teachers tend to focus on completing the curriculum; Less learning time; difficulty communicating with parents; Not all parents are willing and able to accompany their children to study at home; Parents have difficulty understanding lessons and motivating children when accompanying learning at home; Students have difficulty concentrating in learning from home and complain about the many assignments from the teacher.